Effects of Acute Hypoxia and Reoxygenation on Physiological and Immune Responses and Redox Balance of Wuchang Bream (Megalobrama amblycephala Yih, 1955) - Chen, Nan; Wu, Meng; Tang, Guo-Pan; Wang, Hui-Juan; Huang, Chun-Xiao; Wu, Xin-Jie; He, Yan; Zhang, Bao; Huang, Cui-Hong; Liu, Hong; Wang, Wei-Min; Wang, Huan-Ling (Frontiers in Physiology, 2017)
The present study was focused on physiology changes, innate immune responses, oxidative stress statuses in M. amblycephala treated with different oxygenation concentration and time, including control (dissolved oxygen, DO: 5.5 mg/L), 0.5 h acute hypoxia (DO: 3.5 and 1.0 mg/L respectively), 6 h comparable-acute hypoxia (DO: 3.5 mg/L) and then 24 h reoxygenation. The results revealed that hypoxia affected serum hemoglobin (Hb), methemoglobin (MetHb), glucose, Na+, succinatedehydrogenase (SDH), lactate acid (LD) and hepatic glycogen levels, which showed the increase except hepatic glycogen with the decrease of DO level. With the extension of hypoxia time, Hb, MetHb, glucose and LD were increased except Na+, SDH and hepatic glycogen levels, while all above investigated indexes were decreased after reoxygenation. With the decrease of DO level, interferon alpha (IFNα) and lysozyme (LYZ) were gradually increased, whereas albumin was decreased. However, albumin and LYZ levels were decreased after 6 h comparable-acute hypoxia, and remained at high levels after reoxygenation. On the other hand, the liver SOD and CAT, reactive species hydrogen peroxide (H2O2) and total ROS were all remained at lower levels under hypoxia. Finally, Hif-1α levels in liver, spleen and gill were increased with the decrease of DO level and prolongation of hypoxia time. The two Hsp70 isoforms were found in all detected tissues after hypoxia-reoxygenation treatment, whereas internal ribozyme entry site (IRES)-mediated junior Hsp70 was only detected in liver, spleen and gill. Taken together, these results suggest that hypoxia affect M. amblycephala physiology, immune and liver oxidative stress levels.